1978
DOI: 10.1002/path.1711260210
|View full text |Cite
|
Sign up to set email alerts
|

Splenic lipofuscinosis in mice

Abstract: Autopsy examination of young adult mice revealed a characteristic pigmentation of the anterior splenic pole occurring in a high proportion (8-34 per cent) of three mouse strains and two sublines. Histological studies identified the pigment as lipofuscin and electron microscopy provided supporting evidence. Preliminary results are consistent with the hypothesis that lipofuscin may represent non metabolisable debris from cellular breakdown associated with lysosomal activity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

1981
1981
2013
2013

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 20 publications
0
10
0
Order By: Relevance
“…To assess aortic fatty streak lesion development, all sections were stained with oil red O and quantitatively examined for lipid deposition in the wall of the aortic root as previously described (15)(16)(17) ( 19). The absence ofthis property may be related to the degree of oxidation or polymerization of lipofuscin components.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…To assess aortic fatty streak lesion development, all sections were stained with oil red O and quantitatively examined for lipid deposition in the wall of the aortic root as previously described (15)(16)(17) ( 19). The absence ofthis property may be related to the degree of oxidation or polymerization of lipofuscin components.…”
Section: Methodsmentioning
confidence: 99%
“…Quantitative assessment of aortic fatty streak formation in the (BXH) RI strains revealed nonparental phenotypes (Table VII), indicating the involvement of multiple independent genetic factors or a major genetic effect with modi- (19,27). In contrast to cardiac lipofuscin, the occurrence of splenic lipofuscin in C57BL/6J and related strains was only 10-50%, making genetic analysis difficult.…”
Section: Methodsmentioning
confidence: 99%
“…An increasing number of cells containing lipofuscin-like pigments were detected 4 hours after the last DNR injection (Figure 2C). Elevated levels of lipofuscin-like pigments have been found in the spleen of mice subjected to ionising radiation [18], and could be due to accumulation of non-degradable debris in for instance macrophages [19]. The number of cells positive for lipofuscin-like pigments decreased during the next 20 hours (Figure 2C), as was seen for pyknosis and TUNEL-positive cells (Figure 2A).…”
Section: Resultsmentioning
confidence: 86%
“…About 16 ± 7% of back skin was of black colour indicating anagen/early catagen, while the rest -85% was probably in telogen/late catagen/ early anagen. However, in the skin of old animals the pigmented spots might develop in a similar way as in humans, due to deposition of poorly degraded melanin or lipofuscin (Kent, 1976;Crichton et al, 1978;Goyarts et al, 2007). Therefore -a histological examination of skin was performed to show that, indeed, in old mice various hair follicles were in different stages of hair cycling.…”
Section: Figure 2 Association Of Macroscopic Splenic Melanosis With mentioning
confidence: 99%
“…Some authors identify the melanin-bearing splenic cells as "melanophores" (Van der Heijden et al, 1995) akin to melanocytes. The occurence of splenic melanosis varies between particular reports (10-21%, Weissman, 1967;8-34%, Crichton et al, 1978;15%, Veninga et al, 1989;23%, van der Heijden et al, 1995;14-80%, Plonka et al, 2005b) but rarely exceeds 30% (34% for female C57BL/6J and 31% for female C57BL/IOScSn, Crichton et al, 1978; 50-80% for female C57BL/6 in late catagen/early telogen, Plonka et al, 2005b). As the reason of this pigmentatory effect some authors suggested haemosiderins (Veninga et al, 1989) or lipofuscin (Crichton et al, 1978), but most of them, starting with Weissman (1967) and followed by Sundberg (1991), van der Heijden et al (1995, and recently by us (Plonka et al, 2005b), insist that melanin is the pigment responsible for the phenomenon.…”
Section: Introductionmentioning
confidence: 97%